Geração de resíduos de serviços de saúde na cidade de Santarém/Pa - AQUINO, Raissa Pinto de (Universidade Federal do Oeste do Pará, 2024)
Health service waste, also known as hospital waste, is generated in human or animal health establishments such as laboratories and veterinary clinics, which present risks to human health and the environment and can be classified into different categories according to their characteristics and potential risks. The objective of this study was to quantitatively evaluate the generation of health service waste in public and private companies in the municipality of Santarém-PA in the years 2021 and 2022. Data on the monthly generation of waste provided by two collection companies were used, in addition to numbers of confirmed cases of COVID-19 respiratory infection in the municipality of Santarém-PA obtained from the Federal Government database. The data was tabulated in Excel generating graphs in order to compare the monthly generation of 2021 and 2022 according to each group of establishments generating this waste in the municipality. The problem of solid waste management is always a concern in the world, and with the arrival of the COVID-19 pandemic, the management of this waste has become even more necessary due to the complex highly contagious nature of the virus, since infectious waste has increased due to the number of cases registered.